Philosophy without intuitions - Cappelen, Herman (Oxford : Oxford University Press, 2012)
The standard view of philosophical methodology is that philosophers rely on intuitions as evidence. Herman Cappelen argues that this claim is false, and reveals how it has encouraged pseudo-problems, presented misguided ideas of what philosophy is, and misled exponents of metaphilosophy and experimental philosophy.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Methodology; Intuition; Evidence